2021
DOI: 10.1109/tnnls.2021.3082015
|View full text |Cite
|
Sign up to set email alerts
|

4S-DT: Self-Supervised Super Sample Decomposition for Transfer Learning With Application to COVID-19 Detection

Abstract: Due to the high availability of large-scale annotated image datasets, knowledge transfer from pre-trained models showed outstanding performance in medical image classification. However, building a robust image classification model for datasets with data irregularity or imbalanced classes can be a very challenging task, especially in the medical imaging domain. In this paper, we propose a novel deep convolutional neural network, we called Self Supervised Super Sample Decomposition for Transfer learning (4S-DT) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…With the emerge of deep neural networks (DNNs) [ [9] , [10] , [11] , [12] , [13] , [14] ], especially convolutional neural networks (CNNs), they leverage multi-level layer neural networks for representational learning and are widely used for image classification [ 15 , 16 ], object detection [ 17 , 18 ] and semantic segmentation [ 19 ]. Naturally, DNNs are very good at detecting COVID-19 [ [20] , [21] , [22] , [23] , [24] , [25] ]. However, mainly due to lack of interpretability and practical skills, applying DNNs into CXR images for COVID-19 clinical diagnosis has run into obstacles [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the emerge of deep neural networks (DNNs) [ [9] , [10] , [11] , [12] , [13] , [14] ], especially convolutional neural networks (CNNs), they leverage multi-level layer neural networks for representational learning and are widely used for image classification [ 15 , 16 ], object detection [ 17 , 18 ] and semantic segmentation [ 19 ]. Naturally, DNNs are very good at detecting COVID-19 [ [20] , [21] , [22] , [23] , [24] , [25] ]. However, mainly due to lack of interpretability and practical skills, applying DNNs into CXR images for COVID-19 clinical diagnosis has run into obstacles [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Abbas et al in [70] applied a self-supervised learning algorithm to predict COVID19 in CXR images. A combination of deep CNNs, transfer learning, clustering algorithms gave 99.8% on two massive datasets by feeding unlabeled images.…”
Section: Emerging Issues In Covid19 Predictionmentioning
confidence: 99%
“…Using deep learning technology, a number of research studies have been conducted to investigate automated radiographs of the lungs to distinguish patients with pneumonia and COVID-19. Many authors investigated the performance of transfer learning approaches for COVID-19 screening [12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Narin et al [15], for example, created three CNN-based models using the current transfer learning architecture and found that the ResNet model had the best classification accuracy.…”
Section: Related Workmentioning
confidence: 99%